A Case of Cerebral Amyloid Angiopathy-Related Inflammation With the Rare Apolipoprotein ε2/ε2 Genotype - Xu, Yin-Yan; Chen, Shuai; Zhao, Jian-Hua; Chen, Xi-Ling; Zhang, Jie-Wen (Frontiers in Neurology, 2019)
Cerebral amyloid angiopathy (CAA)-related inflammation (CAA-RI) is a rare CAA variant characterized by acute or subacute encephalopathy, headache, epilepsy, or focal neurological deficits. Radiologically, CAA-RI presents with widespread white matter lesions on brain magnetic resonance imaging in addition to the hemorrhagic imaging features of CAA. Previous studies have found that the apolipoprotein E (ApoE) ε4 allele and ε4/ε4 genotype were over-represented in CAA-RI. The role of the ApoE ε2 allele in CAA-RI, however, is largely unknown, partly due to the rarity of the ε2/ε2 genotype in the general population. The authors report the first case of CAA-RI with the rare ApoE ε2/ε2 genotype. The patient presented with mild clinical symptoms but striking neuroimaging abnormalities. The response to small-dose glucocorticoids was satisfactory. Because ApoE ε2 promotes amyloid β accumulation and fibrinoid necrosis in the cerebral vasculature, the ε2/ε2 genotype, similar to ε4/ε4, may also be a precipitating factor for CAA-RI. To clarify the role of ApoE ε2 in CAA-RI, studies with large sample sizes investigating whether ε2 is more common in patients with CAA-RI than in those with CAA only are warranted.